Dilema Identitas Ganda Koperasi: Optimalisasi Bauran Pemasaran 7p Untuk Mendongkrak Partisipasi Anggota Di Era Ritel Modern - Indra Fahmi; Niken Ababiel (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
Koperasi Serba Usaha (KSU) Budidaya is a multi-purpose cooperative engaged in store services to fulfill members' daily needs. However, in recent years, member participation as customers has experienced a significant decline despite increasing store turnover, where sales transactions are predominantly driven by non-member customers. This study aims to analyze the implementation of the 7P marketing mix (product, price, place, promotion, people, process, physical evidence), measure the level of member participation as customers, and formulate strategic efforts to enhance member participation in the store business unit. The research method uses a descriptive quantitative approach, with data collection techniques through observation, in-depth interviews, and questionnaires distributed to 70 active cooperative member samples. Data analysis utilized interval scale analysis and the Importance Performance Analysis (IPA) method using a Cartesian diagram. The results indicate that the implementation of the marketing mix is in the fairly good to good category, but has not optimally met member expectations. The main priority attributes for improvement (Quadrant I) include product variety completeness, price appropriateness, member-specific promotions, complaint handling, and transaction facilities. Therefore, cooperatives need to optimize the value proposition of the marketing mix to encourage member shopping consistency.